Short-course radiation plus temozolomide in elderly patients with glioblastoma - Perry, James R.; Wick, Antje; Wick, Wolfgang (The New England journal of medicine, 2017)
Glioblastoma is a fatal illness that is associated with a median survival of less than 2 years. Population studies of glioblastoma have shown that survival declines with increasing age,1,2 and the incidence of glioblastoma is increasing, especially among the elderly.3 Older patients have been underrepresented in most randomized trials, in which the average age of participants is approximately 55 years, as compared with the population-based median for patients with glioblastoma of 65 years of age.2 In 2005, a phase 3 trial of radiotherapy alone (60 Gy over a period of 6 weeks) versus radiotherapy plus temozolomide showed longer survival . . .